The Effect of Frequency of Stem Wounds Towards The Growth and Yield of Cassava Renek - Ma'rifah, Fitriatul; Astuti, Agung; Mulyono, Mulyono (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
This study was aimed to investigate the effect of the number and frequency of stem wounds towards the growth and yield of cassava Renek. This study was conducted experimentally in the preparation of a single factor RAKL (Complete Randomized Block Design) which consisted of 4 treatments, namely control treatment, frequency of wounding 1 time before planting, frequency of wounding 2 times before planting, and 1.5 BST. and frequency of wounding 3 times before planting cropping, 1.5 BST and 2.5 BST. Observation parameters include the number of mycorrhizal infections in cassava roots, number of spores, root length, root weight, root dry weight, root proliferation, plant height, shoot fresh weight, shoot dry weight, number of leaves, number of tuber plants, tuber length, tuber diameter, tuber weight per plant, and tuber yield. At the age of 5 months, the frequency of wounding 3 times of mycorrhizal cassava Renek only gave a significant difference in the parameters of root length, root weight, and root dry weight. The best number and frequency of wound treatment in 5-month-old mycorrhizal cassava was the frequency of 1 time before planting had a good effect on the parameters of tuber weight per plant (5.09 kg) and tuber yield (50.91 Ton / Ha).